Musical score representation and retrieval in digital environments - Tolare, Jéssica Beatriz [UNESP]; Fujita, Mariângela Spotti Lopes [UNESP]; de Castro, Fabiano Ferreira (SAGE Publications, 2024)
This article aims to analyse the representation and retrieval of musical scores submitted by netizens or institutions, repositories and digital libraries across various digital environments such as score storage sites. It considers the characteristics of these interfaces and observes how the scores are thematically represented. The method employed in this study was exploratory research to search and retrieve scores, and descriptive research to analyse the thematic representation within these environments. The results reveal that these sites are organized by category, which helps netizens in their search for musical scores. The analysed sites differ in comprehensiveness and organization but have similar features with regard to indexing. Consequently, the study argues for investment in their structure, organization, languages and systems, and professional training.
Keywords: indexing; metadata; Musical score; representation; retrieval